Higher Education Regionalization in East Asia - Choi, Edward W. (International Higher Education, 2017)
While regional actors in the East Asian higher education sphere share a history of collaboration, they implement regionalization schemes largely based on different needs, goals, timetables, and customs. This piece presents a summary of key regionalization efforts and intitial indications for a path forward.